2018
DOI: 10.5539/ijel.v9n1p25
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of the Metacognitive Reading Strategies Employed by EFL College Students in Kuwait

Abstract: The study measured the awareness and use of metacognitive reading strategies among English as a foreign language (EFL) students at a medical college in Kuwait. The college offers a four-year Bachelor of Science in Nursing (BSN) and a two-year Associate Degree in Nursing (ADN). Data collection involved distributing the Metacognitive Awareness of Reading Strategy Inventory (MARSI) online through Google Forms to a sample of 80 students (Mokhtari & Reichard, 2002). Data were analyzed for strategy use, vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 9 publications
(24 reference statements)
1
11
1
Order By: Relevance
“…The trend of problem-solving strategies as perceived by the students seems to be strongly preferred by the students over the other types of strategies. According to Alrabah and Wu (2019), one of the most consistent findings on research on metacognitive strategies is that problem-solving strategies have been preferred by learners from a variety of native languages. Additionally, these findings suggest similar findings to those of Miller (2017) and Dumlaio, et al (2019) in which the respondents tend mostly to perceive problem-solving strategies as the mostly frequently used strategies in comparison with global and support strategies.…”
Section: Problem-solving Strategiesmentioning
confidence: 99%
“…The trend of problem-solving strategies as perceived by the students seems to be strongly preferred by the students over the other types of strategies. According to Alrabah and Wu (2019), one of the most consistent findings on research on metacognitive strategies is that problem-solving strategies have been preferred by learners from a variety of native languages. Additionally, these findings suggest similar findings to those of Miller (2017) and Dumlaio, et al (2019) in which the respondents tend mostly to perceive problem-solving strategies as the mostly frequently used strategies in comparison with global and support strategies.…”
Section: Problem-solving Strategiesmentioning
confidence: 99%
“…They found that the most frequently used strategy was problem-solving followed by global reading strategies and the least were support reading strategies. Alrabah and Wu (2019) also reported a possible effect between years of study and use of strategies among students. Mukhlif and Amir (2017) explored the metacognitive online reading strategies of 50 fourth-year tertiary Iraqi students enrolled at Al-Salam University college.…”
Section: Metacognitive Reading Strategies Awarenessmentioning
confidence: 98%
“…On other contexts similar to the Saudi Arabian one, a few studies have been identified that examined metacognitive reading strategies. Alrabah and Wu (2019), for example, conducted a recent study in Kuwait investigating the awareness and use of metacognitive reading strategies among 80 EFL students at a medical college using Mokhtari and Reichard's (2002) MARSI. The results indicated that students generally have high awareness of metacognitive reading strategies.…”
Section: Metacognitive Reading Strategies Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in various EFL and ESL settings, concerns have been raised about students' unpreparedness to meet college reading requirements, especially where the medium of instruction is dominantly English (Al Seyabi & Tuzlukova, 2015;Cahyono & Widiati, 2006;Moss & Bordelon, 2007;Sivaraman, Al Balushi, & Rao, 2014). Although part of the problem is attributed to students' poor language levels (Snow, 2002), a major reason that the literature often cites is students' lack of reading strategies such as self-planning, self-monitoring, self-regulating and self-evaluating (Tavakoli, 2014;Al Rabah & Wu, 2019;Al-Mekhlafi, 2018). & Sheorey, 2002).…”
Section: Introductionmentioning
confidence: 99%